Community-led responses to COVID-19 within Gypsy and Traveller communities in England: A participatory qualitative research study - Alicia Renedo; Rachel Stuart; Charlotte Kühlbrandt; Pippa Grenfell; Catherine R. McGowan; Sam Miles; Serena Farrow; Cicely Marston (Elsevier, 2023)
Individuals were asked to play an active role in infection control in the COVID-19 pandemic. Yet while government messages emphasised taking responsibility for the public good (e.g. to protect the National Health Service), they appeared to overlook social, economic and political factors affecting the ways that people were able to respond.We co-produced participatory qualitative research with members of Gypsy and Traveller communities in England between October 2021 and February 2022 to explore how they had responded to COVID-19, its containment (test, trace, isolate) and the contextual factors affecting COVID-19 risks and responses within the communities.Gypsies and Travellers reported experiencing poor treatment from health services, police harassment, surveillance, and constrained living conditions. For these communities, claiming the right to health in an emergency required them to rely on community networks and resources.They organised collective actions to contain COVID-19 in the face of this ongoing marginalisation, such as using free government COVID-19 tests to support self-designed protective measures including community-facilitated testing and community-led contact tracing. This helped keep families and others safe while minimising engagement with formal institutions.In future emergencies, communities must be given better material, political and technical support to help them to design and implement effective community-led solutions, particularly where government institutions are untrusted or untrustworthy.